Empathy, religiosity, income, degree of damage influencing altruism of Yolanda victims of Tacloban - Momongan, Mae Ann L.; Pantas, Deona Faye S.; Saludario, Dayra E. (2015)
Every person, nomatter what age, is rational in displaying altruistic acts. Every decision one makes is greatly motivated by factors or variables present in the situation. These factors help them make a choice of either helping the needy person or not. Consequently, the researchers investigated if empathy, religiosity, income, and degree of damage may have influenced the victims of Tacloban from Typhoon Yolanda to show altruistic behaviors to others. Results showed that linear combination of empathy and religiosity was significantly related to altruism, thus using the stepwise regression analysis, the two predictors were overlooked.
Undergraduate thesis (B.A. Psychology)--University of the Philippines, Tacloban
Keywords: Empathy; Religiosity; Income; Degree of damage; Altruism